Infarct Growth in Patients with Emergent Large Vessel Occlusion Stroke Transferred for Endovascular Thrombectomy - Xiangjun Xu; Yujuan Zhu; Yapeng Guo; Hao Wang; Junfeng Xu; Ke Yang; Liang Ge; Yi Sun; Xianhui Ding; Qian Yang; Chuyuan Ni; Xianjun Huang (Neurology and Therapy)
Abstract Introduction Patients with a large vessel occlusion (LVO) stroke who are transferred to a comprehensive stroke center (CSC) for endovascular thrombectomy (EVT) often experience infarct growth. We aimed to investigate the clinical predictors of fast infarct growth and its effect on clinical outcomes. Methods We retrospectively collected EVT data of patients with LVO transferred to our center between March 14, 2019, and June 28, 2022. The absolute rate of Alberta Stroke Program Early Computed Tomography Score (ASPECTS) decay was defined as (ASPECTS primary CT − ASPECTS repeat CT)/elapsed hours. The ratio of relative ASPECTS deterioration was defined as (ASPECTS primary CT − ASPECTS repeat CT)/ASPECTS primary CT. In the primary analysis, the study population was dichotomized into absolute slow progressors and absolute fast progressors using the median absolute rate of ASPECTS decay. Secondary analysis was also conducted using the median relative ASPECTS deterioration ratio, and the study population was categorized into relative fast progressors and relative slow progressors. Favorable outcome was defined as a 90-day modified Rankin Scale (mRS) score ≤ 2. Results We included 309 patients: median age 72 years (IQR 65–77); median National Institutes of Health Stroke Scale (NIHSS) 14 (IQR 11–18). The median absolute rate of ASPECTS decay was 0.42 points/hour and the median relative ASPECTS deterioration ratio was 11.1%. Overall, fast infarct growth was independently associated with worse 90-day outcome (absolute rate of ASPECTS decay: OR = 3.395; 95% CI 1.844–6.250; P < 0.001; relative ASPECTS deterioration ratio: OR = 3.754; 95% CI 2.050–6.873; P < 0.001). In multivariable analysis, fast infarct growth was independently associated with high admission NIHSS, proximal occlusions, and poor collateral status, while intravenous thrombolysis before transfer was negative with fast inter-hospital infarct growth. Conclusions For patients with LVO stroke who are transferred from a PSC to CSC for EVT, the infarct growth rate is highly variable and is strongly associated with 90-day outcomes. Initiation of intravenous bridging therapy before transfer may limit the infarct growth during inter-hospital transfer.